2018
DOI: 10.1177/0046958018771414
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Environment and Disparities in Health Care Access Among Urban Medicare Beneficiaries With Diabetes: A Retrospective Cohort Study

Abstract: Older adults’ health is sensitive to variations in neighborhood environment, yet few studies have examined how neighborhood factors influence their health care access. This study examined whether neighborhood environmental factors help to explain racial and socioeconomic disparities in health care access and outcomes among urban older adults with diabetes. Data from 123 233 diabetic Medicare beneficiaries aged 65 years and older in New York City were geocoded to measures of neighborhood walkability, public tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Second, the findings may have been affected by sampling bias. Our prior research among chronically ill Medicare beneficiaries suggested that Blacks, Hispanics, and dually eligible beneficiaries were more likely to have lapses in E&M visits ( Ryvicker & Sridharan, 2018 ). Thus, the required minimum of four E&M visits during the 3-year study period introduced selection bias to the analytic sample, which we confirmed in exploratory analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the findings may have been affected by sampling bias. Our prior research among chronically ill Medicare beneficiaries suggested that Blacks, Hispanics, and dually eligible beneficiaries were more likely to have lapses in E&M visits ( Ryvicker & Sridharan, 2018 ). Thus, the required minimum of four E&M visits during the 3-year study period introduced selection bias to the analytic sample, which we confirmed in exploratory analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In general, although different area-level health outcomes might share a variety of explanatory variables such as socioeconomic, pollution, delinquency levels, health access, among others; by down scaling, spatio-temporal heterogeneity might arise [20,21,[56][57][58]. To overcome the MAUP, a variety of geo-statistical procedures have been implemented to estimate mortality rates at different granularity levels.…”
Section: Spatio-temporal Interpolationmentioning
confidence: 99%
“…Access to health care and disparities in physical health issues occur in the general population, and there is a wealth of evidence that racial and ethnic minorities have less access to services and lower health care service utilization (Manuel, 2018; Ryvicker & Sridharan, 2018). For example, people of color are more likely to have higher rates of high BP, cardiovascular disease, and obesity (Lackland, 2014; Petersen et al, 2019), but they are less likely to access and utilize physical health care (Substance Abuse and Mental Health Services Administration [SAMHSA], 2015).…”
Section: Introductionmentioning
confidence: 99%